2008
DOI: 10.4137/bcbcr.s511
|View full text |Cite
|
Sign up to set email alerts
|

The Reality in the Surveillance of Breast Cancer Survivors—Results of a Patient Survey

Abstract: Background: International guidelines for the surveillance of breast cancer patients recommend a minimized clinical followup including routine history and physical examination and regularly scheduled mammograms. However, the abandonment of scheduled follow-up examinations in breast cancer survivors remains a contradiction to established follow-up guidelines for other solid tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Follow-up tests themselves also may cause psychosocial and physical harm in healthy survivors owing to false-positive findings, unnecessary investigations, and overtreatment [ 16 ]. Despite these reports, both patients and physicians in actual clinical situations do not perform present follow-up guidelines and conduct a variety of surveillances under the belief that intensified follow-up will increase diagnostic security and survival [ 10 , 11 ]. In other words, despite the evidence of well-designed randomized controlled trial, there are still a lot of debates on optimal follow-up modality, frequency, and duration for breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up tests themselves also may cause psychosocial and physical harm in healthy survivors owing to false-positive findings, unnecessary investigations, and overtreatment [ 16 ]. Despite these reports, both patients and physicians in actual clinical situations do not perform present follow-up guidelines and conduct a variety of surveillances under the belief that intensified follow-up will increase diagnostic security and survival [ 10 , 11 ]. In other words, despite the evidence of well-designed randomized controlled trial, there are still a lot of debates on optimal follow-up modality, frequency, and duration for breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…In actual clinical situation, however, most breast cancer survivors want to receive more examinations because they are afraid of the recurrence when conducting follow-up after the primary treatment. Many physicians also tend to perform more tests more frequently than the extent recommended by the guidelines under the belief that they can increase the survival rate despite lack of evidence [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in other medical disciplines, patients may get reassurance, satisfaction with their care, a stronger sense of control, or may value the prognostic information gained from testing . In the field of oncology, surveillance testing specifically has been shown to provide reassurance . On the other hand, surveillance imaging may cause harm.…”
Section: Recommendationsmentioning
confidence: 99%
“…First, the patient-driven anxiety and the feeling of reassurance induced by intensive postoperative surveillance, including the BS. Stemmler et al have examined 801 questionnaires of German women with a history of BC and reported that more than 47.8% of them needed an intensive schedule, which increased their feeling of security [ 27 ]. Second, patients with early or limited metastatic recurrence may be curable; thus, the monitoring of asymptomatic patients could result in better efficacy of BC treatment, at least in theory, when tumor burden is low [ 26 ].…”
Section: Discussionmentioning
confidence: 99%